Body weight in relation to hours of sleep, and physical activity in latin american university students during the Covid-19 pandemic - Meza Miranda, Eliana Romina (2022)
Fil: Meza Miranda, Eliana Romina. Universidad Nacional de Asunción. Centro Multidisciplinario de Investigaciones Tecnológicas; Paraguay